Museum in Crisis: The Past on Sale - Krstović, Nikola M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper focuses on the critical analysis of structural and value deficiencies of the museum scene in Serbia evident in the transfer of the elements of strategic and legislation documents when applied to practical solutions. The position from which the deficiencies are observed is in the current ICOM Strategic plan and its motto “Independence, integrity, professionalism”. These three components of museum work represent the backbone of the musealisation process if it is considered as an activity of museum experts. The paper is structured in the way that follows strategic and legislation documents that are partially or in full considering the museum work in Serbia, and particularly in the segments of decision making. Deficiencies are vertically deliberated—from the concepts in (unacknowledged) the Strategy of Culture Development in Serbia, via in effect the Act on Culture and the Act on Museums to the resulted system of governance and management and, finally, insufficiently developed system of valorisation of basic museum expertise and professional promotion. Through these instances one can observe limitations and inabilities of this socially responsible activity—care for collective memory—to reach its full estimated potential. The reason is easier to verbalize then to argue—almost complete political influence on governance and management of museum institutions followed by incompetence and/or lack of (political) will of decision makers to structure the filed according to contemporary principals of the profession.
Keywords: museum field; management and governance; legislation; politization of profession